Relationship Between Knowledge And Maternal Employment Status With Exclusive Breastfeeding In Infants 0-6 Months In Administrative Districts Fattened Baolan Tolitoli - Haryati, Haryati; Ansar, Muhammad; Kunoli, Firdaus J; Bungawati, Andi (PROMOTIF: Jurnal Kesehatan Masyarakat, 2016)
Exclusive breastfeeding is breastfeeding only to infants from birth to months old, without the addition of other liquids and other food additives. Efficacy of milk may decrease the risk of babies suffering from various diseases. In the region of Puskesmas Baolan Tolitoli in 2015 in the know about exclusive breastfeeding coverage of 54.3%. This study aims to relations knowledge and maternal employment status with exclusive breastfeeding in infants aged 0-6 months working area of Puskesmas Baolan Tolitoli 2015. Kind of research is analytic survey with the draft â€œcross sectional studyâ€.Sampel In this research were 137 respondents in the District Baolan Regency Village Tambun Tolitoli.Cara sampling is random sampling. Based on the test results of Chi-Square dengan value of p = 0.033 (> 0.05), meaning there is no relationship between the mother's knowledge by giving exclusive breastfeeding in infants 0-6 months. The test results obtained statistical p value = 0.000 (<0.05), meaning that there is a significant relationship between maternal employment status with exclusive breastfeeding in infants 0-6 months. The conclusion of this study based on the results of research there are no relationships of the variables knowledge Exclusive breastfeeding mothers with babies 0-6 months and there is a relationship of maternal employment status variables with exclusive breastfeeding in infants 0-6 months in the Village Tambun subdistrict Baolan Tolitoli. Keywords : KnowLedge Job Status Mother, Exclusive Breastfeeding, Baby.